Cambridge First Certificate. Practice Tests 2 for the First Certificate in English Examination: student's book - Stephens N. Nicholas (London, Heinle Cengage Learning, 2009)
Cambridge First Certificate Practice Tests 2 has been revised in line with the updated Cambridge First Certificate in English examination (FCE). The tests have been designed to familiarise students with the exact format of the new examination as well as to expand their vocabulary and to improve the skills required in the examination.